Complex presentation of Bouveret syndrome: Gastric outlet obstruction and septic complications - Mena Louis, DO; Bolaji Ayinde, MD; Nathaniel Grabill, MD; Brian Gibson, MD (Radiology Case Reports)
Bouveret syndrome, a rare form of gastric outlet obstruction, occurs when a large gallstone migrates through a cholecystoenteric fistula into the duodenum, causing obstruction. We report a 31-year-old female who initially presented with nausea, vomiting, and abdominal pain. Imaging identified a large, calcified gallstone, a hepatic abscess, and acute cholecystitis. Initial treatment involved drainage of the hepatic abscess and antibiotics, with plans for elective cholecystectomy. Three years later, she returned with recurrent symptoms, including early satiety, significant weight loss, and gastric outlet obstruction. Endoscopy confirmed duodenal obstruction, and further imaging revealed a cholecystoduodenal fistula. She underwent an open cholecystectomy with fistula excision, duodenal repair, and nasojejunal feeding tube placement. Her postoperative recovery was smooth, with a gradual return to enteral nutrition. This report presents essential diagnostic and treatment approaches for Bouveret syndrome, including the roles of imaging, endoscopy, and surgery in managing complex cases. Early recognition and a coordinated, individualized treatment plan are crucial to optimizing outcomes in this rare condition.